Peroxisomes in plant reproduction and seed‐related development. Issue 7 (22nd February 2019) - Pan, Ronghui; Liu, Jun; Hu, Jianping
Abstract: Peroxisomes are small multi‐functional organelles essential for plant development and growth. Plant peroxisomes play various physiological roles, including phytohormone biosynthesis, lipid catabolism, reactive oxygen species metabolism and many others. Mutant analysis demonstrated key roles for peroxisomes in plant reproduction, seed development and germination and post‐germinative seedling establishment; however, the underlying mechanisms remain to be fully elucidated. This review summarizes findings that reveal the importance and complexity of the role of peroxisomes in the pertinent processes. The β‐oxidation pathway plays a central role, whereas other peroxisomal pathways are also involved. Understanding the biochemical and molecular mechanisms of these peroxisomal functions will be instrumental to the improvement of crop plants. Abstract : Peroxisomes are multi‐functional subcellular compartments crucial to plant development and metabolism. This review summarizes findings that reveal the importance and complexity of the role of peroxisomes in plant reproduction, seed development, seed germination and seedling establishment. The involvement of β‐oxidation and other peroxisomal pathways needs to be further elucidated mechanistically.